2021
DOI: 10.7554/elife.69198
|View full text |Cite
|
Sign up to set email alerts
|

A sex-specific evolutionary interaction between ADCY9 and CETP

Abstract: Pharmacogenomic studies have revealed associations between rs1967309 in the adenylyl cyclase type 9 (ADCY9) gene and clinical responses to the cholesteryl ester transfer protein (CETP) modulator dalcetrapib, however, the mechanism behind this interaction is still unknown. Here, we characterized selective signals at the locus associated with the pharmacogenomic response in human populations and we show that rs1967309 region exhibits signatures of positive selection in several human populations. Furthermore, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“… 8 , 9 In addition, the CETP target gene for dalcetrapib and the ADCY9 effect modifier gene, both residing on chromosome 16, have shown evidence of co-evolution through human history, possibly through a selection pressure. 11 Further evidence of an interplay between these two gene products was obtained from genetically modified mice, with ADCY9 inactivation clearly protecting from atherosclerosis and improving endothelial function only in the absence of CETP. 10 In contrast to the effect on cholesterol efflux, the increase of HDL-cholesterol with dalcetrapib in patients is not dependent on the genotype at position rs1967309 in the ADCY9 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 9 In addition, the CETP target gene for dalcetrapib and the ADCY9 effect modifier gene, both residing on chromosome 16, have shown evidence of co-evolution through human history, possibly through a selection pressure. 11 Further evidence of an interplay between these two gene products was obtained from genetically modified mice, with ADCY9 inactivation clearly protecting from atherosclerosis and improving endothelial function only in the absence of CETP. 10 In contrast to the effect on cholesterol efflux, the increase of HDL-cholesterol with dalcetrapib in patients is not dependent on the genotype at position rs1967309 in the ADCY9 gene.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Furthermore, the demonstrated relationship between ADCY9 and CETP during recent human evolution has pointed towards a biological link between dalcetrapib’s effect modifier gene ADCY9 and its therapeutic target CETP. 11 The multiple observed interactions between ADCY9 and CETP in both animals and patients suggested that they represent a real biological phenomenon and not a spurious statistical association. Accordingly, we designed and conducted the dal-GenE study to test prospectively the pharmacogenetic hypothesis that dalcetrapib provides cardiovascular benefits when administered to patients with the favourable genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Adcy9 was a target gene of piR-dre-332 and piR-dre-5797. Adcy9 , which encodes an adenylyl cyclase [ 57 , 58 , 59 , 60 ], can regulate the metabolism associated with the estrogen receptor pathway and is a sex-specific gene in patients with coronary artery disease [ 61 , 62 ]. In addition, adcy9 is a female-inclined gene that is regulated by an estrogen-related receptor (ERR) to modulate ovarian development in the giant freshwater prawn ( Macrobrachium rosenbergii ) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human genetics can also inform on subgroup effects in the context of precision medicine, for clinical trial design, or to assess the external validity of drug effects on other patient populations. Genetic studies of CETP variants have highlighted possible effect modification by sex on HDL-c levels, carotid intima-media thickness, the HDLc/apoAI ratio, and on the dynamics of postprandial triglyceride levels (Anagnostopoulou et al, 2009;Christen et al, 2018;Gamache et al, 2021;Kark et al, 2000;Klingel et al, 2017). Sex differences were also observed in many traits thought to be involved in the atheroprotective effect of CETP such as the apoAI and apoA-II composition of HDL and CETP-mediated cholesterol efflux (Schaefer et al, 1982;Villard et al, 2013).…”
Section: Discussionmentioning
confidence: 99%